Fluctuating Asymmetry and Environmental Stress: Understanding the Role of Trait History - De Coster, Greet (Public Library of Science, 2013)
While fluctuating asymmetry (FA; small, random deviations from perfect symmetry in bilaterally symmetrical traits) is widely regarded as a proxy for environmental and genetic stress effects, empirical associations between FA and stress are often weak or heterogeneous among traits. A conceptually important source of heterogeneity in relationships with FA is variation in the selection history of the trait(s) under study, i.e. traits that experienced a (recent) history of directional change are predicted to be developmentally less stable, potentially through the loss of canalizing modifiers. Here we applied X-ray photography on museum specimens and live captures to test to what extent the magnitude of FA and FA-stress relationships covary with directional shifts in traits related to the flight apparatus of four East-African rainforest birds that underwent recent shifts in habitat quality and landscape connectivity. Both the magnitude and direction of phenotypic change varied among species, with some traits increasing in size while others decreased or maintained their original size. In three of the four species, traits that underwent larger directional changes were less strongly buffered against random perturbations during their development, and traits that increased in size over time developed more asymmetrically than those that decreased. As we believe that spurious relationships due to biased comparisons of historic (museum specimens) and current (field captures) samples can be ruled out, these results support the largely untested hypothesis that directional shifts may increase the sensitivity of developing traits to random perturbations of environmental or genetic origin.